Association between Eye Donation Awareness of Next-of-Kin and Eye Donation after Grief Counselling - Puri, Oshin; Gupta, Neeti; Mittal, Sanjeev Kumar (Nepalese Journal of Ophthalmology, 2026)
Introduction: Corneal transplantation is a definitive treatment for corneal blindness, but only 25% patients receive corneas due to donor scarcity. Community awareness initiatives increase willingness to donate, but little is known about how awareness influences actual donation. Objective: To assess the association between pre-existing eye donation awareness of the next-of-kin and donation after grief counselling. Methodology: The 164 most stable next-of-kin were enrolled in this analytical cross-sectional study with due consent and ethical approval. Participants were approached by the Eye Donation Counsellor (EDC). After assessing their awareness about eye donation through the Ronanki “Awareness and Perception on Eye Donation” questionnaire, the EDC grief counselled the next-of-kin. Result: Thirty-four (20.7%) brothers and 33 (20.1%) fathers of the deceased were the most stable next-of-kin. In total 139 (84.8%) participants were aware of eye donation. The mean awareness, knowledge, and perception scores of the study population were 2.46 ± 1.34 out of 4, 2.73 ± 2.37 out of 6, and 1.79 ± 1.72 out of 4, respectively. Eye care professionals (105, 64.02%) and mass media (61, 37.19%) were identified as the most common sources of information. While 86 (52.4%) expressed willingness to donate, only 12 (7.31%) donated, and there was one (0.61%) voluntary donation. Counselling and the belief that eye donation is a noble deed were identified as the major motivators. Chi-square (x2) and p-value for the association between eye donation and the pre-existing awareness of the next-of-kin were 0.95 and 0.33, respectively, suggesting no significant association. However, awareness was associated with the increased willingness to donate eyes (x2 = 19.35; p-value <0.001). Conclusion: There was no significant association between eye donation and awareness of the next-of-kin.